COMUNIDADE QUILOMBOLA DE SÃO DOMINGOS REGIÃO DO SAPÊ DO NORTE/ES: ASPECTOS ETNOLINGUÍSTICOS COM ÊNFASE NO LÉXICO - Borges, Jardiléia Pereira (2021)
This work constitutes a research on the speeches present in the Quilombola São Domingos community, located in the region of Sapê do Norte – ES. The main objective was to present the community and territory of Sapê highlighting the ethnolinguistic aspects with an emphasis on the lexicon. In the analysis chapter, after the transcriptions of the interviews using the transcription key of the strands project, we discuss some lexicons such as: CAMARINHA, ABADÔ, ALABÊ, EPÔ, GUINÉ and MARIÔ present in the speeches of the residents of this space. The lexicons collected in the interviews were mapped and treated according to the corpus of Castro (2001), who uses in his research a vocabulary composed of 3,517 lexicons, words and expressions found in speeches from Bahia: an Afro-Brazilian vocabulary. The relevance of this study in the São Domingos community points to a significant contribution to the Sapê do Norte region, and with that, it becomes an extremely relevant element for the academic universe of the North Capixaba. For this, we carried out the field research and selected three residents, taking as reference the criteria of gender and age group. The result of this work, even though it was interrupted by the pandemic, allows us to state that the slavery period in the Sapé do Norte region, the traffic from the port of São Mateus – ES and the lexical proximity of African languages at that time, preserved for a period, a feature language not yet known. Thus, there was a need to continue this study for analysis of possible lexicons of African and indigenous origin. This is because this theme is unprecedented in the region, therefore, with this research and the resumption of this theme, it is intended to contribute to linguistic studies and teaching of the Portuguese language.